PARTISIPASI PUBLIK DALAM PEMERINTAHAN: MEMBANGUN DEMOKRASI PARTISIPATIF DI ABAD KE-21 - Melyana R Pugu (CV. Adiba Aisha Amira, 2025)
Public participation in government is a mainstay of participatory democracy in the 21st century. The active involvement of citizens in the decision-making process increases the legitimacy of government and results in policies that are more in line with the needs of the community. In the digital age, technology has expanded access and opportunities for public participation, enabling more transparent and direct interaction between government and citizens. However, challenges such as the digital divide and the potential for information misuse remain and must be addressed with inclusive strategies. Hence, the importance of public participation, the role of technology in facilitating citizen engagement, and the steps that can be taken to overcome obstacles in order to realise a strong and sustainable participatory democracy.